HUBUNGAN KETERAMPILAN PENGELOLAAN KELAS OLEH GURU PAK DENGAN MOTIVASI BELAJAR SISWA - Juli Tri Desima Pasaribu (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2018)
Abstract, This Research aim to know which are positive and signifikan skill of Management of class By Teacher Christian of Religion with Motivation Learn Student class of VIII SMP N 7 Sibolga Year Study 201702018. This research represent quantitative Descriptive research, where becoming its population entire/all class student of VIII SMP N 7 study year sibolga 2017 / 2018 which believe in Christian Protestant amounting to 120 people, while sampel the used 25% from amount of population namely 30 people. Because titemttable hence research hypothesizing accepted, hence this research conclude the existence of which are positive and signifikan Skill Of Management Of Class By Teacher Christian of Religion with Motivation Learn Student Class of VIII SMP N 7 Sibolga Year Study 2017 / 2018 and hypothesizing in this research accepted.